Martínez Garrido, Elisa; Rodríguez Fierro, Mercedes (eds.) (2002) Italo Svevo «La conciencia de Zeno» - Piero Dal Bon (Swervei de publicacions, 2005)
Martínez Garrido, Elisa; Rodríguez Fierro, Mercedes (eds.) (2002) Italo Svevo La conciencia de Zeno